1998
DOI: 10.1111/j.1749-6632.1998.tb09899.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Mutation to Mitochondrial DNA and Age‐dependent Decline of Mitochondrial Respiratory Functiona

Abstract: Mitochondrial respiration and oxidative phosphorylation are gradually uncoupled, and the activities of the respiratory enzymes are concomitantly decreased in various human tissues upon aging. An immediate consequence of such gradual impairment of the respiratory function is the increase in the production of the reactive oxygen species (ROS) and free radicals in the mitochondria through the increased electron leak of the electron transport chain. Moreover, the intracellular levels of antioxidants and free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
130
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(138 citation statements)
references
References 104 publications
3
130
0
5
Order By: Relevance
“…Previous studies on lymphocytes revealed an increase of reactive oxygen species (ROS) in aged subjects (Schindowski et al, 2000) or elevated by-products caused by ROS (e.g. lipidperoxidation (Hendricks and Heidrick, 1998), oxidized proteins (Stadtman, 1992;Berlett and Stadtman, 1997) and DNA-damage (Wei et al, 1998)). Altered and impaired signal transduction, in general, seems to be a major cause for impaired cellular function in all aged tissues (Eckert et al, 1994;Mü ller et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on lymphocytes revealed an increase of reactive oxygen species (ROS) in aged subjects (Schindowski et al, 2000) or elevated by-products caused by ROS (e.g. lipidperoxidation (Hendricks and Heidrick, 1998), oxidized proteins (Stadtman, 1992;Berlett and Stadtman, 1997) and DNA-damage (Wei et al, 1998)). Altered and impaired signal transduction, in general, seems to be a major cause for impaired cellular function in all aged tissues (Eckert et al, 1994;Mü ller et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus, oxidative injury to mtDNA causes mutations in mitochondrial genes and/or results in the generation of abnormal proteins in the electron transport system. 6,7 Furthermore, mitochondrial membrane injury could also be induced via lipid peroxidation reactions in the presence of ROS. 8 Mitochondria are the major source of reactive oxygen species even in their normal state.…”
mentioning
confidence: 99%
“…Cells may break down mitochondria when they are not working properly or when it ages [9]. A lot of mitochondrial proteins are encoded in the nucleus.…”
Section: Journal Of Phylogenetics and Evolutionary Biologymentioning
confidence: 99%
“…Most likely, free radicals damage mitochondria causing release of components. A growing body of evidence has established that the levels of Reactive Oxygen Species and oxidative damage to lipids, proteins, and nucleic acids are significantly increased with age in animal and human tissues [9].…”
Section: Journal Of Phylogenetics and Evolutionary Biologymentioning
confidence: 99%